2010
DOI: 10.5617/adno.1057
|View full text |Cite
|
Sign up to set email alerts
|

Valg og gjennomføring av videregående opplæring før Kunnskapsløftet

Abstract: Norge har en videregående opplæring med en ambisiøs målsetting: flest mulig skal oppnå studie- eller yrkeskompetanse og utdanning skal bidra til å jevne ut sosiale forskjeller. I denne artikkelen viser vi at realiteten er annerledes: Om lag sju av ti i hvert årskull fullfører og består, mens tre av ti enten slutter før tida eller gjennomfører hele løpet uten å bestå i alle fag. Gjennom analysene viser vi at rekrutteringen til yrkesfaglige henholdsvis studieforberedende utdanningsprogrammer så vel som utfallet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 2 publications
1
18
0
8
Order By: Relevance
“…The most important variable for GPA in upper-secondary schools is GPA in lower-secondary school. This is also consistent with previous national and international research (Haegeland & Kirkebøen, 2007;Hattie, 2009;Markussen, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most important variable for GPA in upper-secondary schools is GPA in lower-secondary school. This is also consistent with previous national and international research (Haegeland & Kirkebøen, 2007;Hattie, 2009;Markussen, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…A number of Norwegian studies have shown high correlations between GPA in lower-secondary school and grades in upper-secondary school, choice of education program and dropout (e.g., Haegeland & Kirkebøen, 2007;Markussen, 2010). Such findings also correspond with the international literature, and Hattie (2009) concludes that prior achievement is a powerful predictor throughout the education system.…”
Section: Independent Variablesmentioning
confidence: 72%
“…In both countries there are different definitions and methods of calculating rates, and in both countries one should be careful when defining the various events. In Norway this most of all concerns the terms frafall, omvalg, bortvalg and gjennomføring, which are often used inconsistently (Markussen, Frøseth, Lødding, Sandberg, 2008;Markussen, 2011) Apprenticeship contract termination and dropout from VET: a comparison of educational-political challenges and strategies in Norway and Switzerland Lehrstellenwechsel and Lehrabbruch. In both countries, this can be the case in certain occupations and sectors such as hairdressers, bricklayers and the hospitality trade.…”
Section: Apprenticeship Contract Termination and Dropoutmentioning
confidence: 99%
“…Leaving home at an early age entails different kinds of transitions, and moving away from home at this age, while simultaneously attending a new school, seems to affect adolescents’ well-being, creating the risk of dropping out of school and/or potential mental health problems (Markussen, 2005, 2011). An increase in mental health problems in adolescents, especially among girls, during the last 20 years has been identified (Bor, Dean, Najman, & Hayatbakhsh, 2014; Collishaw, 2015; Von Soest & Wichstrøm, 2014).…”
Section: Introductionmentioning
confidence: 99%